Efficacy of ventriculoperitoneal shunting in patients with cryptococcal meningitis with intracranial hypertension. (November 2019) - Liu, Ying; Peng, Xiaohua; Weng, Weizhen; Zhu, Jianyun; Cao, Hong; Xie, Shibin
Highlights: An obvious decline in intracranial pressure (ICP) and Cryptococcus count was seen in the ventriculoperitoneal (VP) shunt patients. There was less usage of mannitol and improved hydrocephalus or ventriculomegaly for those who underwent VP shunting. The clearance time of Cryptococcus and the hospitalization time were shortened. VP shunting can be considered for patients diagnosed with cryptococcal meningitis with apparent ICP. VP shunting is also suggested for those with no hydrocephaly, but with apparent ICP. Abstract: Background: Ventriculoperitoneal (VP) shunting in cryptococcal meningitis (CM) patients with high intracranial pressure (ICP) has been studied extensively. Methods: A total of 74 CM patients with ICP were identified, including 27 patients with or without ventriculomegaly receiving VP shunting. Results: Through retrospective analysis, there was an obvious decline in ICP as well as Cryptococcus count after VP shunting. Damage to the cranial nerves was improved after the surgery. For those patients receiving VP shunting, there was an obvious decline in ICP as well as Cryptococcus count, with less usage of mannitol. Hydrocephalus or ventriculomegaly was improved, and both the clearance time of Cryptococcus and the hospitalization time were shortened ( p  < 0.05). The complications of VP shunting were not common. Conclusions: For patients diagnosed with CM and with apparent ICP, VP shunting can be considered regardless of whether there is damage to the cranial nerves or hydrocephaly.